(3JKHjJ GdLfS hGKGQg (B:s (3OQGSI ebGQfI ai Gdabg GdGSdGei hGdbGfhf GdeOfi (B/ s - (3GdTgGHi GHQGgje GdTQbGhis; (3Ydi MSjf fLjOIs; (3eMehO HdGd egQGfs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2002)
(3JfGhdfG gPg GdQSGdI aj ebOeI hHGH JegjOi hCQHYI CHhGH hJhUjGJ hNGJeI (B. (3hGfJgjfG ef NdGdgG Edi Cfg dG hLhO eG jSei (B( (3JZjjQ GdLfS (B) (3, hCf GdeUWdM GdYdej GdUMjM ddLQGMGJ GdWHjI GdJj jUHM GdTNU Ydi CKQgG PcQkG HYO Cf cGf XGgQg CfKi Ch GdYcS gh eUWdM (B( (3JKHjJ GdLfS (B) (3, hCf eYjGQ eTQhYjI Jdc GdLQGMI jcef HMSH OdGdI GdaJGhi GdabgjI aj chf GdeQjV NJai hdG jcef aj QZHJg GdTNUjI hdG aj eLQO fbU GdPchQI Ch GdCfhKI(B. (3hGSJYQVfG ehba GdJTQjY hGdabg hGdbVGA aj GdYOjO ef GdOhd hGfJgjfG Edi Cfg aj ZGdHjfg bO JYOi GdGYJQGb deTQhYjI LQGMI JKHjJ GdLfS Edi GdGYJQGa HLQGMGJ GdeSN GdeMQeI TQYkG (B. (3hGbJQMfG aj gPG GdNUhU JTcjd dLfI JVe eJNUUjf aj GdYdhe GdWHjI hGdTQYjI hGdbGfhfjI dJbhe Ydi CeQ GdLQGMI(B.. (3hfGOjfG HhMOI GdeSFhdjI aj GdeLGd GdWHj(B. (3hGSJYQVfG BKGQ JKHjJ GdLfS aj eNJda GdfhGMj GdTQYjI hGdbGfhfjI (B: (3hhVYfG Hjf jOi GdeTQY eTQhY bGfhf dJfXje GdLQGMI eMd GdHMK , Ke CNjQkG ef NdGd GdNGJeI hVYfG eHGOiA YGeI dJMce BKGQ JKHjJ GdLfSs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdeOfi, (B2002s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B601-621s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdeOfjs; (3Gdabg GdGSdGeis; (3eYUhejI GdLSOs; (3JKHjJ GdLfSs; (3GdNfKi GdMbjbjs; (3GdJCfjK GdNUhjs; (3BKGQ JKHjJ GdLfSs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs